2019
DOI: 10.3390/cells8111425
|View full text |Cite
|
Sign up to set email alerts
|

Identification of A Novel Class of Benzofuran Oxoacetic Acid-Derived Ligands that Selectively Activate Cellular EPAC1

Abstract: Cyclic AMP promotes EPAC1 and EPAC2 activation through direct binding to a specific cyclic nucleotide-binding domain (CNBD) within each protein, leading to activation of Rap GTPases, which control multiple cell responses, including cell proliferation, adhesion, morphology, exocytosis, and gene expression. As a result, it has become apparent that directed activation of EPAC1 and EPAC2 with synthetic agonists may also be useful for the future treatment of diabetes and cardiovascular diseases. To identify new EPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…However, it should be noticed that these effects might also result form off-target effects due to the possible interaction of these activators with Epac2 and PDEs [114]. Recently, novel small molecule activators have been identified that displays greater selectivity towards Epac1 [117,118]. Their impact on cardiac remodeling and fibrosis still need to be tested.…”
Section: Exchange Protein Activated By Campmentioning
confidence: 99%
“…However, it should be noticed that these effects might also result form off-target effects due to the possible interaction of these activators with Epac2 and PDEs [114]. Recently, novel small molecule activators have been identified that displays greater selectivity towards Epac1 [117,118]. Their impact on cardiac remodeling and fibrosis still need to be tested.…”
Section: Exchange Protein Activated By Campmentioning
confidence: 99%
“…The potency and the specificity shown towards Epac1 positions 8-CPT as the gold standard ligand for Epac1 activation in vitro and in vivo. However, other compounds are being developed; the first non-nucleotide agonist of Epac1, I942, for example, was isolated by Beck and collaborators (2019) [ 93 ]. Structural analysis showed that I942 was capable of interacting with the CNB domain of both Epac1 and Epac2, but it displayed partial agonist properties only towards Epac1 [ 93 ].…”
Section: Role Of Epac1 In Cardiac Pathophysiologymentioning
confidence: 99%
“…However, other compounds are being developed; the first non-nucleotide agonist of Epac1, I942, for example, was isolated by Beck and collaborators (2019) [ 93 ]. Structural analysis showed that I942 was capable of interacting with the CNB domain of both Epac1 and Epac2, but it displayed partial agonist properties only towards Epac1 [ 93 ]. The group of Yarwood performed systematic modifications on I942 and then structure–activity relationship studies and found four new compounds (25e, 25f, 25n, and 25u) that showed better specificity and higher activity for Epac1 [ 94 ].…”
Section: Role Of Epac1 In Cardiac Pathophysiologymentioning
confidence: 99%
“…Another non-cyclic nucleotide, SY009 agonist was isolated by ultra HTS in a library of 350,000 compounds. SY009 is chemically distinct from I942 and displays higher selectivity for EPAC1 over EPAC2 and PKA [ 36 ]. Subsequent studies must be performed to investigate the functional effects of these compounds.…”
Section: Epac1 Pharmacological Modulatorsmentioning
confidence: 99%